Aceh Shariah Court in The Unitary State of the Republic of Indonesia and Human Rights Context - Rifqi Ridlo Phahlevy (Universitas Muhammadiyah Sidoarjo, 2014)
Birth of Special Region Nanggroe Aceh Darussalam based on Law No. 18/2001 on Special Autonomy for Aceh as Nanggroe Aceh Darussalam that changed through Law No. 11 of 2006 on the Governing of Aceh is an attempt to realize a democratic government and prosperous (welfare state). The implication of the birth of NAD is the application of Islamic law as a tool of law and governance NAD, which also puts the Shariah Court as the main pillar of Islamic sharia enforcement in NAD. The existence of the Shariah Court as an instrument of law enforcement in NAD institutionally and functionally problematic. The first, related to the position of the Shariah Court that institutionally a part of the religious court, but has a broader scope of authority. Second, related to aspects of Islamic sharia holding capacity is possible to be imposed on non-Muslims, were both these problems can ultimately hurt the Unitary Republic of Indonesia principles and protection of human rights. How To Cite: Phahlevy, R. (2014). Aceh Shariah Court in The Unitary State of the Republic of Indonesia and Human Rights Context. Rechtsidee, 1(1), 71-84. doi:http://dx.doi.org/10.21070/jihr.v1i1.103